Treatment of industrial oleochemical wastewater by electrocoagulation method - Rebecca, Stephen (2015)
Production of oleochemical products which derived from biological plant oils and animal fats which react in form of triglycerides with different composition of the alkyl chains which will form fatty acid methyl ester (FAME), fatty alcohols, fatty amines and glycerin can generates wastewater that contain fatty acids, glycerin, organic residues and inorganic acids which really need to be treated before being discharged to the environment especially into any water bodies. Therefore, a research must be conducted to find the solution for this problem. In this study, the potential to treat oleochemical wastewater using electrocoagulation (EC) process was studied. The oleochemical wastewater was collected from FPG Oleochemical Sdn Bhd which is situated in Gebeng, Pahang. The objectives of the study are to determine the optimum operational conditions such as initial pH of wastewater samples, type of electrodes, applied voltage or current density, reaction time and electrodes arrangement for the EC process of oleochemical wastewater in terms of removing the parameters of chemical oxygen demand (COD), oil and grease (O&G) and total suspended solids (TSS) of wastewater. The final pH and turbidity of treated wastewater samples also being determined. Furthermore, there is also a primary treatment or pre-treatment methods that being used to reduce the concentration of the glycerine from wastewater sample. The experiment results show that EC could effectively reduce COD, O&G, TSS and turbidity by 55.72%, 68.48%, 77.46% and 90.31% respectively using aluminium electrode at the optimum conditions of pH 6, applied voltage 20 V and reaction time of 30 minutes. In addition, the experimental results also show that the electrocoagulation can neutralize pH of wastewater. The result that will be obtained will be compared to the Standard A & B of Parameter Limit of Effluent as being outlined by Department of Environment based on Environmental Quality Act 2009.